The School to Deportation Pipeline: The Perspectives of Immigrant Students and Their Teachers on Profiling and Surveillance within the School System. Issue 1 (September 2017) - Verma, Saunjuhi; Maloney, Patricia; Austin, Duke W.
Ample research has identified links between school and the criminal justice system; our work builds on these studies by identifying the pathway to deportation that immigrant students face. Our qualitative study, conducted in seven U.S. cities, focused on recent immigrant students and their teachers in secondary education institutions. We evaluated the intersection of race and immigrant backgrounds to understand their compounded effects on racialization processes. We found that racial identity formation among recent immigrants is shaped by experiences of tracking and profiling within the school system as well as surveillance practices around school spaces. We argue that racialization—the process by which students come to be regarded (by themselves or the broader society) as a part of the U.S. racial paradigm—is a critical mechanism by which immigrant students enter a school to prison to deportation pipeline.